Robert Owen, James Buchanan et l’Infant School de New Lanark - Marie Vergnon (Recherches en Éducation)
The history of infant education puts a lot of emphasis on the New Lanark Infant School and its founder, the Scottish reformer Robert Owen. Although Owen is commonly credited with the authorship of this school, one of his former teachers, named James Buchanan, contends with him for the original idea. What is the share of each of those two men in the creation of this original structure? Was Buchanan more than the first teacher of the Infant School? It is mostly through Owen’s writings that we know this educational experience. Those texts constitute our memory of the genesis of the Infant School and provide us with a few pieces of information about the pedagogy that was used there. May other resources enable us to shed light on the respective roles of the first protagonists of the Infant School and to clarify the way this institution worked? This research aims at giving some answers to those questions shrouding the origin of one of the first collective infant education structures.